2010
DOI: 10.1111/j.1751-7176.2009.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency and Functional Impact of Overlapping Hypertension on Hypertrophic Cardiomyopathy: A Single‐Center Experience

Abstract: Between 1995 and 2005, 196 adults with hypertrophic cardiomyopathy (HCM) were evaluated. Among these, 122 (62%, group 1) patients also had systemic hypertension. The clinical presentation, management, outcome, and echocardiographic findings of these patients were compared with 74 (38%, group 2) patients without systemic hypertension. Patients in group 1 were older at the time of HCM diagnosis and had a higher prevalence of diabetes (28% vs 9%; P=.02) and coronary artery disease (40% vs 25%; P=.03). In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 14 publications
2
26
0
3
Order By: Relevance
“…Nonetheless, patients with HCM generally display greater thickness of both the interventricular septum (frequently >15 mm) and the posterior wall (frequently >11 mm) than patients with VSB2 16 (figure 3). Normal posterior wall thicknesses (ie, <11 mm) have been generally reported in VSB studies1 14 15 as compared with HCM studies in the elderlies, in which some degree of hypertrophy was also involving the posterior wall 25 29 30. Thus, a less severe degree of hypertrophy and a normal posterior wall thickness may potentially help differentiate between patients with VSB and elderly patients with HCM.…”
Section: Echocardiographymentioning
confidence: 90%
See 1 more Smart Citation
“…Nonetheless, patients with HCM generally display greater thickness of both the interventricular septum (frequently >15 mm) and the posterior wall (frequently >11 mm) than patients with VSB2 16 (figure 3). Normal posterior wall thicknesses (ie, <11 mm) have been generally reported in VSB studies1 14 15 as compared with HCM studies in the elderlies, in which some degree of hypertrophy was also involving the posterior wall 25 29 30. Thus, a less severe degree of hypertrophy and a normal posterior wall thickness may potentially help differentiate between patients with VSB and elderly patients with HCM.…”
Section: Echocardiographymentioning
confidence: 90%
“…Unfortunately, no standard method of quantification of MAC exists, and both echocardiography (figure 3) and X-ray-based imaging modalities have been used to screen for the presence and severity of MAC. MAC has been demonstrated in about 30%–70% of elderly subjects with both HCM9 25 29 31 and VSB 14 15. Some studies also suggested a higher prevalence of MAC when hypertension was associated 14 29.…”
Section: Echocardiographymentioning
confidence: 99%
“…16 Well-conducted prospective non-HCM studies link increasing BP and incident hypertension with the presence and severity of SDB, independent of confounding variables (especially age, sex, and obesity). 17 Th e physiologic nocturnal decrease in BP is attenuated in patients with SDB, resulting in the so called nondipping BP pattern.…”
Section: Hypertensionmentioning
confidence: 99%
“…saopštili da je konačni ishod netretirane hipertenzije kongestivna srčana slabost [6]. Aslam F. i saradnici su analizirali 196 individua sa ehokardiografskom prezentacijom hipertrofične kardiomiopatije, pri čemu je 62% bolovalo od arterijske hipertenzije [7]. Ova studija ukazuje na čestu pojavu sekundarne hipertenzivno hipertrofične kardiomiopatije.…”
Section: Uvodunclassified